Immediate implant placement with simultaneous regenerative procedure in fresh extraction socket - de Molon, Rafael S. [UNESP]; de Avila, Erica D. [UNESP]; Barros-Filho, Luiz Ab. [UNESP]; Cirelli, Joni A. [UNESP]; Borelli-Barros, Luiz A. [UNESP] (Jaypee Brothers Medical Publishing, 2017)
Aim: The aim of this case report was to reconstruct the alveolar buccal bone plate lost in consequence of a root fracture in the maxillary central incisor area after immediate implant placement (IIP). A 48-year-old patient was referred to our office with the chief complaint of spontaneous bleeding in his left central incisor. After careful examination, the following comprehensive treatment approach was carried out: (1) Atraumatic tooth extraction, (2) IIP, (3) provisional prosthesis installation, (4) alveolar buccal bone plate reconstruction with autologous bone collected from the maxillary tuberosity, (5) gingival augmentation procedure with connective tissue graft removed from the palate, and finally (6) adjustment of the provisional restoration. After 1-year postoperative, an adequate esthetic outcome was achieved with lower cost, reduced morbidity to the patient, and lower treatment time. This approach was able to improve gingival architecture and bone volume with adequate thickness and width, enhancing patient esthetics and satisfaction. In conclusion, when proper diagnosis, precise surgical techniques, and appropriate multidisciplinary approach are employed, IIP followed by immediate dentoalveolar restoration might be considered a safe procedure to restore the peri-implant bone and gingival recession favoring the achievement of appropriate esthetic outcomes. Clinical significance: The treatment planning employed was able to improve gingival architecture and bone volume with sufficient width and thickness enhancing patient esthetics and satisfaction in one single-stage procedure.
Keywords: Alveolar bone loss; Connective tissue; Esthetics; Immediate dental implant